An assessment of operations of oil-exporting countries in terms of energy consumption and carbon dioxide emissions. (6th November 2008) - Ramanathan, Ramakrishnan
Energy consumption and carbon dioxide emissions from 16 oil-exporting countries are studied using Data Envelopment Analysis using indicators representing economic growth, energy consumption and emissions. The analysis for 1996 shows that Norway, Gabon and Nigeria are efficient and that Russia is inefficient. Malmquist Productivity Index analysis shows that there is progress in achieving higher values of GDP and non-fossil fuel consumption and in achieving lower values of fossil fuel consumption and carbon emissions in the year 1996 when compared with 1992 for Norway, Russia, Mexico, Algeria, Libya, Gabon and Oman.